Anh văn chuyên ngành (Kế toán) - ThS. Trần Kim Ngân (Trường Đại học Trà Vinh, 2024)
Chapter 1. Introduction to accounting and basic terminology in accounting. Chapter 2. Analysing transactions and making entries. Chapter 3. Adjusting accounts and completing accounting cycle. Chapter 4. Stating English terminology of accounting for inventory. Chapter 5. Accounting for merchandising businesses. Chapter 6. Preparation and analysis of financial statements in English. Problem series